Integrating biodiversity into land use planning: Research contributions - Stoms, D. M. (American Planning Association National Planning Conference, 2001)
Preservation of biodiversity is one of the most contentious environmental issues in the United States. Researchers have made progress in improving our understanding of the impacts of development but this has not led to much improvement in planning tools. This talk will offer a conceptual framework for addressing biodiversity-related planning questions. A model for selecting new biological reserves will be described, both to illustrate some of the lessons learned and future directions needed to incorporate biodiversity management into the larger arena of land use planning. The key to progress is better integration among scientists from different disciplines.